Plant growth regulators increase yield of Pyrus communis L. 'Williams' pear in Southern Brazil - Luz A.R.* (2014)
Poor fruit set is one of the biggest problems faced by pear growers in Brazil. Inadequate fertilization of the ovules results in lower fruit set and lower yields in pears. When pollination is insufficient, it is necessary to use plant growth regulators (PGRs) to increase fruit set and fruit production. The objective of the present study was to evaluate the potential for different plant growth regulators to increase productivity of 'Williams' pear trees. Randomized complete block design experiments were conducted during three growing seasons in São Francisco de Paula city (29°05'S, 50°50'W, alt. 869 m), Rio Grande do Sul State, Brazil. The treatments were: 1 - water control; 2 - gibberellic acid 4 and 7 (GA4+7) + 6-benzyladenine (6-BA) 6 mg/L applied at the beginning, full and end of bloom; 3 - prohexadione calcium (ProCa) 340 mg/L at full bloom (FB); 4 - ProCa 680 mg/L at FB; 5 - ProCa 340 mg/L 15 days after full bloom (DAFB); 6 - aminoethoxyvinylglycine (AVG) 300 mg/L 15 DAFB; 7 - GA4+7 + 6BA 18 mg/L at FB followed by AVG 300 mg/L 15 DAFB; 8 - GA4+7 + 6BA 18 mg/L at FB followed by AVG 150 mg/L 15 DAFB; 9 - GA4+7 + 6BA 18 mg/L at FB followed by ProCa 170 mg/L 15 DAFB, and 10 - Thidiazuron (TDZ) 20 mg/L at FB. Fruit set, yield, fruit diameter and number of non-viable seeds per fruit were evaluated. Trees sprayed with GA4+7 + 6BA (6 mg/L) x 3, ProCa 680 mg/L at FB, GA4+7 + 6BA at FB followed by AVG (150 or 300 mg/L) at 15 DAFB, and TDZ (20 mg/L) at FB showed increase on the fruit set and estimated productivity compared to the control.